Medical involvement in procreation in Greek Law (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
Greek Family Law already quite early (since 2002) provided for a modern legal framework regulating the medical involvement in procreation. The legislator proved his social sensitivity regarding the right of citizens to reproduce by passing Law 3089/2002, which was pioneering. The author has set out to briefly analyze conditions for the implementation of art. 1455 of the Greek Civil Code and the consent to artificial insemination and its withdrawal.
Keywords: medically assisted human reproduction; Artificial insemination; consent; conditions; legal capacity